Herbivorous turtle ants obtain essential nutrients from a conserved nitrogen-recycling gut microbiome - Yi Hu (Nature Portfolio, 2018)
Gut bacteria are prevalent across insects including ants, but their precise roles are often unclear. Here, Hu et al. show that microbes aid ants by recycling nitrogen into bio-available amino acids. This function is conserved across the turtle ants, suggesting an ancient nutritional mutualism.